Professional Android 4 application development - Meier, Reto (John Wiley & Sons, 2012)
19 chapters: Hello, Android; Getting Started; Creating Applications and Activities; Building User Interfaces; Intents and Broadcast Receivers; Using Internet Resources ; Files, Saving State, and Preferences; Databases and Content Providers; Working in the Background; Expanding the User Experience; Advanced User Experience;...